Bipolar disorder in Iceland : effect of treatment, frequency of suicide attempts, employment status and recovery experience - Hulda María Frostadóttir 1989- (2023)
Increased knowledge of bipolar disorder in recent years has led to the development of new treatment options. The number of specialized clinics for bipolar disorder has increased in many parts of the world with the aim of improving the health and quality of life for people with bipolar disorder. The aim of this study was to investigate the effects of the current treatment provided by the bipolar outpatient service at Landspítali University Hospital. Furthermore, the purpose is to examine the frequency of psychiatric hospitalizations, suicide attempts among the individuals seeking treatment at the bipolar outpatient service, along with their employment, study, and disability benefits status, as well as their recovery experience. The goal is to gain insight that can help tailor the service to better meet the needs of these patients. Participants were individuals seeking service from the bipolar outpatient service at Landspítali University Hospital. The self-report scale, BRQ, was used to measure personal experiences of recovery. The result showed a significant reduction in the number and length of hospitalizations after participants entered into bipolar outpatient service. The findings also showed that 29.23% of the participants (n = 19) had attempted suicide at some point in their lives which is consistent with the literature, and that majority of the participants, or 62.5% (n = 60), were employed and/or studying, which is a higher percentage than the literature has shown. Finally, recovery experience had a significant relationship with whether participants were working or not and whether participants were dealing with anxiety or depression. Participants that were working and/or studying scored higher on The BRQ than those who were not working. Also, participants that did not meet the criteria for anxiety or depression scored higher on the BRQ than those who met the criteria. Keywords: Bipolar disorder, bipolar outpatient service, hospitalization, suicide attempt, quality of life, employment, study and ...